‘Awareness, Attitude and Application of Knowledge among Rural Women: A Case Study of Kasargod in Kerala’ - Himanshu Tripathi and Sunita Yadav (International Journal of Innovative Knowledge Concepts, 2018)
In this paper an attempt has been made to know the situation of rural woman with regard to three dimensions of knowledge: awareness, attitude and application (3A). For the study, it is assumed that weak socio-economic background of a rural woman is pulling her back in every aspect of life. So, it is necessary to empower them by education/training. A training pogramme is developed to make women aware of their rights and privileges. The training package is applied upon 20 women village leaders (Group A) of Kasargod district in Kerala for two weeks in Jun 2017 to strengthen their awareness, attitude and application of knowledge (3A). These 20 women imparted non-formal training to 280 females (Group B) for three months from Jul 2017 to Sep 2017 in their respective areas. Later, the sample of 300 females was tested on an achievement test to know the effectiveness of training in terms of women’s awareness, attitude and application (3A). In the study it is found that 20 socio-economically sound females are much stronger in personal empowerment attributes than 280 females who have more strength in social empowerment area. There is change in the attitude of Group B females after the training. Group B is now more positive towards gaining knowledge and becoming aware of their rights. Though their changed attitude is not liked by their male family members. In the application field, Group B women are weaker than Group A. So, we can conclude that socio-economic factor is affecting woman’s empowerment. The time has come to make them more empowered by the way of education. Apart from education and training, it is the duty of their family members to invoke women for their position and participation in every field of life equally.